A multiple-network poroelastic model for biological systems and application to subject-specific modelling of cerebral fluid transport. (February 2020) - Guo, Liwei; Vardakis, John C.; Chou, Dean; Ventikos, Yiannis
Abstract: Biological tissue can be viewed as porous, permeable and deformable media infiltrated by fluids, such as blood and interstitial fluid. A finite element model has been developed based on the multiple-network poroelastic theory to investigate transport phenomenon in such biological systems. The governing equations and boundary conditions are adapted for the cerebral environment as an example. The numerical model is verified against analytical solutions of classical consolidation problems and validated using experimental data of infusion tests. It is then applied to three-dimensional subject-specific modelling of brain, including anatomically realistic geometry, personalised permeability map and arterial blood supply to the brain. Numerical results of smoking and non-smoking subjects show hypoperfusion in the brains of smoking subjects, which also demonstrate that the numerical model is capable of capturing spatio-temporal fluid transport in biological systems across different scales.